Pengaruh Pengembangan Karir, Komitmen Organisasi, Kepuasan Kerja dan Stres Kerja terhadap Turnover Intention Karyawan pada PT. Hyunki Abhimata Perkasa Palembang - Emelda Yani; Yunidar Erlina; Ernawati; Noviarni; Ellen Sumiarni (Equivalent : Journal of Economic, Accounting and Management, 2024)
Abstract : This research aims to determine whether there is an influence of Career Development, Organizational Commitment, Job Satisfaction and Job Stress on the Turnover Intention of PT Hyunki Abhimata Perkasa Palembang employees. The population and sample in this study were 43 people from all employees of PT Hyunki Abhimata Perkasa Palembang. The analysis technique used is multiple linear analysis which is processed using the Statistical Product and Service Solution (SPSS) version 25 computer program. The research results show that there is an influence of Career Development, Organizational Commitment, Job Satisfaction and Job Stress on the Turnover Intention of PT Hyunki Abhimata Perkasa Palembang employees. With a significant F of 0.000<0.05. Multiple linear regression equation 5.109+0.001X1–0.088X2– 0.032X3 + 0.328X4 + e. There is no influence of career development on employee turnover intention at PT Hyunki Abhimata Perkasa Palembang with a significant value of 0.996>0.05. There is no influence of organizational commitment on employee turnover intention at PT Hyunki Abhimata Perkasa Palembang with a significant value of 0.485 > 0.05. There is no influence of job satisfaction on employee turnover intention at PT Hyunki Abhimata Perkasa Palembang with a significant value of 0.781>0.05. There is an influence of work stress on employee turnover intention at PT Hyunki Abhimata Perkasa Palembang with a significant value of 0.002 <0.05. Abstrak : Penelitian ini bertujuan untuk mengetahui apakah ada pengaruh Pengembangan Karir, Komitmen Organisasi, Kepuasan Kerja dan Stres Kerja Terhadap Turnover Intention karyawan PT Hyunki Abhimata Perkasa Palembang. Populasi dan sampel dalam penelitian ini sebanyak 43 orang dari seluruh karyawan PT Hyunki Abhimata Perkasa Palembang. Teknik analisis yang digunakan adalah analisis linier berganda yang diolah dengan menggunakan bantuan program computer Statistical Product and Service Solution (SPSS) versi25. Hasil penelitian menunjukan bahwa ada pengaruh Pengembangan Karir, Komitmen Organisasi, Kepuasan Kerja dan Stres Kerja Terhadap Turnover Intention karyawan PT Hyunki Abhimata Perkasa Palembang. Dengan signifikan F sebesar 0,000<0,05. Persamaan regresi linear berganda 5.109+0,001X1–0,088X2– 0,032X3 + 0,328X4 + e. Tidak terdapat Pengaruh Pengembangan Karir TerhadapTurnover Intention Karyawan PT Hyunki Abhimata Perkasa Palembang dengan nilai signifikan sebesar 0,996>0,05. Tidak Terdapat Pengaruh Komitmen Organisasi Terhadap Turnover Intention Karyawan PT Hyunki Abhimata Perkasa Palembang dengan nilai signifikan sebesar 0,485 > 0,05. Tidak Terdapat PengaruhKepuasan Kerja Terhadap Turnover Intention Karyawan PT Hyunki Abhimata Perkasa Palembang dengan nilai signifikan sebesar 0,781>0,05. Terdapat Pengaruh Stres Kerja Terhadap Turnover Intention Karyawan PT Hyunki Abhimata Perkasa Palembang dengan nilai signifikan sebesar 0,002 <0,05.